The Effect of Weather, Price, Product Quality on Purchasing Decisions of Semarang Residents - Alfredo, Figo De; martawijaya, Elang ilik (Jurnal Ilmiah Manajemen Kesatuan, 2024)
Repurchase intention is the most important target in marketing, especially for Semarang residents who have weather that tends to be hotter during the day. The habit of consuming cold drinks due to needs and weather effects also affects shopping behavior for Semarang residents. Iced tea itself is not foreign to Indonesian people. The purpose of this study is to determine the role of weather moderation in the influence of brand image, product quality and price on consumer attitudes and their impact on repurchase intention. This type of research is correlational with a quantitative approach. The sample used was 200. The data collected was processed using (PLS-SEM). Brand Image, Product Quality, Price affect Consumer Attitudes and Consumer Attitudes affect Repurchase Intentions. Weather has a moderating effect on the influence of Brand Image and Price on Consumer Attitudes. The need to improve brand image through providing customer ideas, creating digital marketing that is considered effective and conducive, with good quality marketing packaging in order to produce a better perception for the product and further researchers should expand the scope of research variables.